Saving water in schools: evidence on the use of smart water meters and behavioural insights - Berger, Kenneth John (School of Economics, 2020)
The city of Cape Town suffered a severe water crisis in 2018. At the peak of the drought in South Africa’s Western Cape, a randomised control trial at 105 schools investigated the impact of two behavioural interventions to encourage responsible water usage: detailed water usage data feedback from smart meters, and an interschool competition. Interventions reduced water usage in these schools by 15 to 26%. The information feedback was found to be more effective in reducing night time water use, indicating better water usage by the staff, while the competition was found to be more effective during the day time, indicating better water usage by the pupils. The contrast highlights the way feedback was understood differently by the two groups, with different effects on their assumption of responsibility. This example from Cape Town demonstrates the effectiveness of combining smart technologies with nudges. It provides a model of water conservation interventions for sustainable cities.